1999
DOI: 10.1097/00006534-199903000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Expansion in the Reconstruction of Tessier Craniofacial Clefts: A Series of 17 Patients

Abstract: Tessier craniofacial clefts are among the most surgically challenging examples of craniofacial dysmorphology. These clefts are characterized by hypoplasia of soft-tissue and skeletal elements throughout the three-dimensional extent of the cleft. Whereas bone grafting and craniofacial osteotomies have been successful toward correcting the underlying skeletal abnormalities, the ultimate success of these reconstructions has been limited by the deficiency of skin and soft tissue. This deficiency demands reconstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 13 publications
0
29
0
Order By: Relevance
“…General surgical options, including multiple local flaps with or without tissue expansion, for complex Tessier 3 clefts in combination with a multitude of other craniofacial anomalies are usually presented as case reports or small series. [6][7][8][9][10][11][12][13] While most report some degree of long-term follow-up, there is often little description of secondary procedures and no standardized discussion of topographic landmarks or reproducible measurements to develop a standardized approach to management. A reconstructive algorithm based on soft tissue and bony involvement has been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…General surgical options, including multiple local flaps with or without tissue expansion, for complex Tessier 3 clefts in combination with a multitude of other craniofacial anomalies are usually presented as case reports or small series. [6][7][8][9][10][11][12][13] While most report some degree of long-term follow-up, there is often little description of secondary procedures and no standardized discussion of topographic landmarks or reproducible measurements to develop a standardized approach to management. A reconstructive algorithm based on soft tissue and bony involvement has been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…4 Menard et al 5 reported tissue expansion in the reconstruction of a series of Tessier craniofacial clefts: primary correction of facial clefts and preparation for bone grafting or osteotomy. They concluded that long-term bone graft viability demanded coverage with tissue of adequate vascularity and that tissue expansion was effective in tension-free reconstruction for osteotomy and bone grafting.…”
Section: Discussionmentioning
confidence: 99%
“…Correction with the other local flaps will be planned in the near future. Tissue expansion or free tissue transfer are good alternatives for soft tissue recon- struction (Toth et al, 1990;Longaker and Siebert, 1996;Menard et al, 1999). Caudal displacement of the palpebral fissure and cephalic rotation of the ala was noted in case 1.…”
Section: Discussionmentioning
confidence: 99%